Social control in hydrocarbon policies: a comparative analysis of indigenous participation in Peru and Ecuador - Mejía Tarazona, Alejandro (Politai, 2017)
In recent years, the incidence of non-state actors and social control have been configured as a public policy problem. fte present article is framed inside of the public policy analysis and for it is used the frame explanatory of the design of the policy through the analysis of the instruments of NATO typology. fte work is structured based on an analysis of congruence that allows to generate a logical coherence of a historical narrative of the countries analyzed. fte case study is the free and informed consultation in the hydrocarbons policies of Peru and Ecuador. fte main argument is that the objectives assumed by the government for the hydrocarbons sector become in the implementation of policies that affecting positively or negatively the social control in the sector. Within a comparative analysis, it is studied how these objectives come to consolidate and to generate a normative and institutional change within the analyzed sector, causing the indigenous participation to be affected in a way that generates a deficit of social control in the Ecuadorian case; and strengthening it for the Peruvian case.